2004
DOI: 10.1021/jp044938g
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect in an Au−Ag Alloy Nanocatalyst:  CO Oxidation

Abstract: Au-Ag alloy nanoparticles supported on mesoporous aluminosilicate have been prepared by one-pot synthesis using hexadecyltrimethylammonium bromide (CTAB) both as a stabilizing agent for nanoparticles and as a template for the formation of mesoporous structure. The formation of Au-Ag alloy nanoparticles was confirmed by X-ray diffraction (XRD), ultraviolet-visible (UV-vis) spectroscopy, and transmission electron microscopy (TEM). Although the Au-Ag alloy nanoparticles have a larger particle size than the monome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
266
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 352 publications
(280 citation statements)
references
References 17 publications
10
266
0
Order By: Relevance
“…The resultant gold catalyst, with an average gold particle size of $5 nm, was only moderately active for low-temperature CO oxidation [63]. Assuming that Ag might be able to assist the activation of oxygen, Mou and co-workers further attempted to synthesize an Au-Ag@MCM catalyst using the same one-pot method [27]. The schematic synthesis procedure is shown in Fig.…”
Section: One-pot Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The resultant gold catalyst, with an average gold particle size of $5 nm, was only moderately active for low-temperature CO oxidation [63]. Assuming that Ag might be able to assist the activation of oxygen, Mou and co-workers further attempted to synthesize an Au-Ag@MCM catalyst using the same one-pot method [27]. The schematic synthesis procedure is shown in Fig.…”
Section: One-pot Methodsmentioning
confidence: 99%
“…The synthesis of Au-Ag and Au-Cu bimetallic NPs has led to great progress in the optical applications [55,56], while it has been less reported for the purpose of catalysis. Mou and Zhang's groups are among the first that reported synergistic effects of Au-Ag [27] and Au-Cu [21] in catalytic reactions.…”
Section: Preparation Of Au-ag and Au-cu Bimetallic Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Crooks and co-workers synthesized PdAu/TiO 2 using dendrimer-encapsulated alloy nanoparticles as the precursor, and found that the activities of the catalysts in CO oxidation followed the sequence PdAu/TiO 2 > Pd/TiO 2 > Au/TiO 2 [235]. Mou and coworkers synthesized AuAg/Al-MCM-41 catalysts via both a one-step approach [236][237][238][239] and a two step method [55], and demonstrated enhanced catalytic activity in CO oxidation associated with the alloyed silver. Zhang and co-workers used a similar two-step approach to prepare AuAg/SiO 2 [53], AuAg/Al 2 O 3 [53], AuCu/SBA-15 [240], and AuCu/silica gel [63] catalysts, and demonstrated their good performance in CO oxidation.…”
Section: In Situ Transformation Of Niau/sio2 Into Au-niomentioning
confidence: 99%
“…Thus, the Au nanoparticles@mesoporous silica can be used as a highefficiency catalyst, particularly for CO oxidation. (13,14) The resulting Au nanoparticles@ mesoporous silica showed catalytic capability of CO oxidation. CO conversion rate increases with increasing reaction temperature and Au nanoparticle content (Fig.…”
Section: Resultsmentioning
confidence: 99%